Bible legends an introduction to Midrash - Freehof, Lillian B. (Simon) 1906- (UAHC Press, 1987)
A collection of Jewish legends focusing on such primary characters of the book of Genesis as Adam and Eve, Noah, Abraham and Rebecca, Jacob, and Joseph.